2015
DOI: 10.1002/jmri.24844
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted imaging: Effects of intravascular contrast agents on apparent diffusion coefficient measures of breast malignancies at 3 tesla

Abstract: Purpose To determine whether apparent diffusion coefficient (ADC) measures of breast lesions at 3 tesla (T) are affected by gadolinium administration. Materials and Methods The study included 19 patients who underwent 3T MRI. Diffusion-weighted imaging (DWI) was acquired with b=0, 100, and 800 s/mm2 before and after a dynamic contrast-enhanced (DCE) sequence. ADC values were measured for each lesion and normal fibroglandular tissue. Pre and post-contrast ADC measures were compared by Wilcoxon signed-rank tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 24 publications
1
40
1
1
Order By: Relevance
“…The influence of contrast administration on DWI is controversial with some studies demonstrating little effect 11,49-51 and others suggesting that the effect may be tissue specific and dependent on image timing after contrast administration 52-56 . Our own data shows that ADCs increase significantly after DCE-MRI in both malignant and normal tissue at 3T, but this effect can be neutralized by using normalized ADCs (see below) 57 . The reason for the observed ADC change requires further investigation.…”
Section: Protocol Optimizationmentioning
confidence: 93%
See 1 more Smart Citation
“…The influence of contrast administration on DWI is controversial with some studies demonstrating little effect 11,49-51 and others suggesting that the effect may be tissue specific and dependent on image timing after contrast administration 52-56 . Our own data shows that ADCs increase significantly after DCE-MRI in both malignant and normal tissue at 3T, but this effect can be neutralized by using normalized ADCs (see below) 57 . The reason for the observed ADC change requires further investigation.…”
Section: Protocol Optimizationmentioning
confidence: 93%
“…ADC normalization may reduce variation from individual breast characteristics and technical factors such as whether DWI is performed pre- or post-contrast 57 . Normalized ADC is calculated as: nADC=ADClesionADCnormal where ADC lesion and ADC normal are the mean ADC of the lesion and normal breast parenchyma tissue, respectively.…”
Section: Diffusion Weighted Imaging Interpretationmentioning
confidence: 99%
“…Overall, the influence of contrast agent administration on breast lesion ADC measures was determined to be negligible [50, 51], particularly when DWI is acquired several minutes post-contrast [51], and either approach is acceptable.…”
Section: Considerations For Clinical Implementationmentioning
confidence: 99%
“…When added to CE-MRI, DWI sequences showed a significant diagnostic gain: the summary ROC-AUC of CE-MRI combined with DWI was 0.94 compared with 0.85 for CE-MRI alone (2). Differently from 1H-MRS, contrast injection does not negatively impact on DWI performance (51); ADC measures were reported to not significantly change following DCE-MRI at 3 T, suggesting that DWI and DCE-MRI can be performed in any order without affecting diagnostic performance (52). Moreover, Janka et al showed that DWI after contrast injection even leads to a slightly better benign/malignant discrimination (53).…”
Section: Diagnostic Performance Of Dwimentioning
confidence: 99%